Kelayakan Aspek Materi dan Media dalam Pengembangan Bahan Ajar Bola Voli Berbasis Kontekstual - Moh. Ali Mu'arifuddin (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
Instructional materials are supporting the success of learning. The purpose is the development of teaching materials to help facilitate the learning process so that learners drafting special requirements that must be met. One of the compulsory subjects in biology education courses are of Volley Ball, and based on the needs analysis, multimedia-assisted teaching materials is very required This research aims to develop products Volley Ball course textbook using the 4D model viable aspect materials and media. The 4D model consists of stages define, design, develop, and disseminate. The development phase is limited to stages develop.This research generates results media and language as validation data. The tests showed that the textbook and interactive multimedia eligible for use in the real learning of Volley Ball course.Validator also put forward suggestions for the improvement of some parts of teaching materials.